All Islam ever wanted was freedom - Omer, Spahic (IIUM, 2019)
In life, there is only truth, as a reflection and confirmation of the Absolute Truth, Almighty Allah (al-Haqq). What we think of and call falsehood is imaginary. It does not really exist. It is only a temporary and conditioned absence of truth. Likewise, there is only light in this earthly life, for Allah is the Light of the heavens and the earth, which is the source and quintessence of the former. There is no actual ontological darkness. Its existence, too, is illusory. What we perceive as darkness is no more than a transient and conditioned absence of light. Even Satan, the incarnation of evil, was not created and preordained as such. He only chose to be so, and was granted by the leave of Allah to operate in such a role until an appointed term. There is nothing that is intrinsically evil. Evil is only that which some people, under the sway of Satan’s whispers, concoct, while manipulating and abusing certain innocent components of life. In other words, evil is a consequence of some people’s devilish creativity. Accordingly, we should never unduly worry about the provisional existence of falsehood and its closest ally, darkness. Neither Satan should be a person’s greatest worry. Rather, what we should worry about is the absence of truth and light. If they are brought about, falsehood and darkness, as a result, will instantaneously fade away and vanish. That is so because the two elements cannot coexist. Truth and light are the antidotes for falsehood and darkness respectively. Similarly, a true believer and servant of Allah is the antidote for Satan and his advances: “Feeble indeed is the cunning (strategy or plots) of Satan” (al-Nisa’, 76). This is the message of the Qur’anic verse (ayah): “And say, ‘Truth has come, and falsehood has perished. Indeed is falsehood, (by nature), ever bound to perish’” (al-Isra’, 81). An example of this is a person who comes for a purpose to a dark room. Certainly, the person will not panic, nor be put off, because of the room’s condition. The only thing he will be concerned about is finding a switch to turn on the lights. That is, he will worry about and attend to the real things. Doing so will solve all his problems. The presence of darkness in the room and its being an obstacle will not even cross his mind. There is darkness in the room just because the lights are turned off. As indispensable as they are, at the heart of truth and light lies freedom. It is their soul. In equal measure, at the center of darkness and falsehood lie denial of freedom and its mishandling. Allah declares: “And say: ‘The truth is from your Lord, so whoever wills - let him believe; and whoever wills - let him disbelieve (reject the truth)’” (al-Kahf, 29). By freedom it is meant not merely to do whatever and whenever one wills. Rather, freedom means to independently know what is needed to be done to self-actualize, and to be able to do it freely without interferences and constraints.